The social biography of the Lublin Diet’s participant (1569): Peter Kisel and Cimafiej Hurka - Padalinski, Uladzimir A. (Journal of the Belarusian State University. History, 2019)
The article explores the biographies of Peter Kisel and Cimafiej Hurka, who represented the Viciebsk district at the Diet of 1569 and directly participated in the conclusion of the Union of Lublin. For a long time in historiography, attention was paid only to the most influential figures of this Diet. However, the simple, «unremarkable» representatives of the wide circles of the Grand Duchy of Lithuania’ nobility played their role in the negotiations on the union. Interests and ideas, conscious and values, and finally, the personal experience of these people directly determined their social and political position, and therefore, to one degree or another, the life of the entire state. The aim of research is to reflect the most important forms of social activity of the Grand Duchy of Lithuania’ petty and middle nobility in the second half of the 16th century on the example of two Viciebsk noblemen’s unique destinies. It shows the influence of the military and political events of the 1560s on political activities of Peter Kisel and Cimafiej Hurka. The Livonian War’s experience definitely influenced their position on the conclusion of the union between the Grand Duchy of Lithuania and the Polish Kingdom in 1569. The author concludes that it was the cardinal transformations of the 1560s (state reforms, the establishment of the Commonwealth) that allowed them to actively participate in a public life of the Grand Duchy of Lithuania. It also enabled Kisel and Hurka noble families to take a firm place among the political elite of the Viciebsk district for a long time. It is emphasized that a detailed study of «unremarkable» noblemen’s biographies provides advanced research of the noble estate of the Grand Duchy of Lithuania.
Keywords: the Union of Lublin; biography; the Grand Duchy of Lithuania; the Commonwealth; nobility; social activity